Undescended testis: an epidemiological study from a single institution - Marcela Almeida Bazaga; Márcia Emília Francisco Shida; Mila Torii Corrêa Leite (Revista Paulista de Pediatria, 2025)
ABSTRACT Objective: The aim of this study was to assess the referral and treatment timelines for patients with undescended testis treated in the Pediatric Surgery Division at Escola Paulista de Medicina/UNIFESP. Methods: Retrospective review of patients treated for undescended testis at a tertiary care institution from 1992 to 2021. Ethical approval was granted by the institutional ethics committee. Data collected included patients’ demographics and clinical characteristics, referral age, age at orchidopexy, testis laterality and position prior to surgery, and duration of postoperative follow-up. A descriptive analysis was performed for each variable, excluding patients with incomplete medical records. Results: In the cohort of 350 patients with undescended testis, 72.6% had unilateral and 27.4% bilateral presentations; and 8% of the patients had differences in sex development. Ultrasound was requested in 19.5% of cases. The average age at referral was 47.3 standard deviation (±) 41.6 months, with 72.5% referred after 18 months. Among 131 orchidopexy procedures, 12.8% were performed before 12 months of age, 15.9% until 18 months, and the majority after 60 months. Of the 120 patients who underwent surgery, only 78.3% had postoperative follow-up data, and 52.1% lost follow-up. The average follow-up period was 23.1±26.20 months. Conclusions: The average age at diagnosis and treatment of undescended testis was higher than recommended by international guidelines, indicating the need for enhanced medical and non-medical community referral practices.